Amelioration of Experimental Hepatotoxicity in Rats by Portulaca oleracea Linn. from Kashmir Himalaya - Dar, Mohd A.; Mir, Prince A.; Masoodi, Mubashir H.; Alqahtani, Ali S.; Siddiqui, Nasir A.; Ahmad, Bahar (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Traditionally, Portulaca oleracea Linn. is used for treating abscesses, dysentery and liver diseases. In addition, recent studies have reported its efficacy as an analgesic, as neuroprotective, anti-inflammatory, bronchodilatory, and anticancer agent, besides antioxidant, wound healing and other important pharmacological actions. Aims and Objectives: For curing liver diseases, Chinese use juice from the fresh leaves of Portulaca oleracea Linn. Hence, to prove this claim, an in-vivo hepatoprotective study of extracts from Portulaca oleracea Linn. against carbon tetrachloride hepatotoxic rats was carried out. Methods: The in-vitro antioxidant activity by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay and hepatoprotective activity of extracts of Portulaca oleracea Linn. was assessed against the carbon tetrachloride-induced toxicity rat model. Results: The extracts of Portulaca oleracea Linn produced concentration-dependent percentage inhibition of 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical and most significantly, by methanol extract. Among the extracts, methanol extract showed a significant decrease in Serum glutamic oxaloacetic transaminase (SGOT), Serum glutamic pyruvic transaminase (SGPT), alkaline phosphatase (ALP) levels and a significant increase in total protein (TP) levels against carbon tetrachloride-induced liver toxicity. Conclusion: From the results obtained, it was concluded that methanol extract of Portulaca oleracea Linn. possesses significant DPPH free radical scavenging and hepatoprotective potential.
Keywords: carbon tetrachloride